Strategi Diversifikasi Produk terhadap Tingkat Omzet Penjualan. Studi Kasus pada PT. Surya Pelita Pratama - Purba, Jan Horas Veriyadi (Jurnal Ilmiah Ranggagading (JIR), 2005)
The purpose of the research is to gain strategy clues on product diversification of housing implemented by a company and to find out how far the company carries out its activity and business in line with product diversification strategy of the housing towards the sales volume. PT Surya Pelita Pratama applied diversification strategy in the beginning of sales in 2003 by launching new type of housing, type 40 and type 50. During the year it increased because of new types. The expenses result in sales increase, because the decision making on strategy implementation is the factor influencing the sales volume or the value of the diversification strategy. By using correlation analysis we can see the positive relation between diversification strategy and sales volume which means that by applying diversification strategy they can increase sales volume of PT Surya Pelita Pratama. Key words: Product Diversification; Sales Volume